Synthesis, phase and microstructure characteristics of Pb(Zr0.52Ti0.48)O3-(Bi3.25La0.75)Ti3O12ceramics - N. Thongmee (2018)
Ceramics with formula (1 - x)Pb(Zr0.52Ti0.48)O3-x(Bi3.25La0.75)Ti3O12(when x = 0, 0.1, 0.3, 0.5, 0.7, 0.9 and 1.0) were prepared by a solid-state mixed-oxide method and sintered at temperatures between 950 °C and 1250 °C. It was found that the optimum sintering temperature was 1150 °C at which all the samples had densities at least 95% of theoretical values. Phase analysis using X-ray diffraction indicated the existence of BLT- as well as PZT-based solid solutions with corresponding lattice distortion. Scanning electron micrographs of ceramic surfaces showed a plate-like structure in BLT-rich phase while the typical grain structure was observed for PZT-rich phase. The grain sizes of both pure BLT and PZT ceramics were found to decrease as the relative amount of the other phase increased. This study suggested that tailoring of properties of this PZT-BLT system was possible especially on the BLT-rich side due to its large solubility limit. © 2007 Elsevier B.V. All rights reserved.